Pseudocapacitive behaviors of Li2FeTiO4/C hybrid porous nanotubes for novel lithium-ion battery anodes with superior performances - Tang, Yakun (2020)
Hybrid nanotubes of cation disordered rock salt structured Li2FeTiO4 nanoparticles embedded in porous CNTs were developed. Such unique hybrids with continuous 3D electron transportation paths and isolated small particles have been shown to be an ideal architecture that brought out enhanced electrochemical performances. Meanwhile, they exhibited improved extrinsic capacitive characteristics. In addition, we demonstrate a successful example to use cathode active material as anode for lithium-ion batteries (LIBs). More importantly, our hybrids had much superior electrochemical performances than most of the reported Li4Ti5O12-based nanocomposites. Therefore, it is concluded that Li2FeTiO4 can be a prospective anode material for LIBs.